Application of polyamide nanofiltration membrane in selective separation of new pollutants and salt ions in water environment
By forming a polyamide selection separation layer on the polymer ultrafiltration membrane carrier, regulating the membrane surface characteristics, solving the problems of new pollutant removal rate and mineral element interception in the prior art, and achieving efficient and economical "high defouling- Low hardness removal" selective separation effect.
Patent Information
- Application Number
- CN202410958557.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-07-17
AI Technical Summary
The prior art is difficult to achieve high removal rate of new pollutants in water environments and low retention of mineral elements such as Ca2+ and Mg2+. The preparation process of nanofiltration membranes is complex and costly, making it difficult to achieve large-scale preparation.
Using a polyamide nanofiltration membrane, a polyamide selection separation layer is formed on the polymer ultrafiltration membrane support to regulate the carboxyl density and zeta potential of the membrane surface to achieve selective separation of new pollutants and salt ions.
It achieves a high retention rate of new pollutants (≥99%) and a low retention rate of salt ions (≤40%), while reducing the preparation cost and process complexity of nanofiltration membranes, making it suitable for large-scale production.
Smart Images

Figure CN118649567B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane separation, and in particular to the application of a polyamide nanofiltration membrane in selectively separating new pollutants and salt ions in a water environment. Background Art
[0002] New pollutants refer to toxic and hazardous chemicals that are discharged into the environment and have characteristics such as biological toxicity, environmental persistence, and bioaccumulation, which pose a great risk to the ecological environment or human health, but have not yet been included in management or the existing management measures are insufficient. Healthy and safe drinking water should remove new pollutants as much as possible while retaining a certain concentration of Ca 2+ Mg 2+ and other mineral elements. In the prior art, conventional deep drinking water treatment processes are mainly based on degradation and adsorption. In order to achieve high removal of new pollutants and Ca 2+ Mg 2+ In order to achieve the goal of low retention, it is urgent to develop a safe and efficient "high pollution removal-low hardness removal" selective separation technology.
[0003] Nanofiltration is a pressure-driven membrane separation technology between ultrafiltration and reverse osmosis. It is highly efficient and energy-saving and is widely used in seawater desalination, wastewater treatment, solvent recovery, drug concentration and purification, and other fields. Different application scenarios require different performance requirements for nanofiltration membranes. For example, lithium extraction from brine requires high monovalent / multivalent ion selectivity, seawater desalination requires high salt rejection, separation of new pollutants requires nanofiltration membranes to have high selectivity for new pollutants, and certain wastewater treatment processes require nanofiltration membranes to have high permeability. Directed regulation of the performance of nanofiltration membranes for different application scenarios is currently a hot topic in the field of nanofiltration membrane research.
[0004] At present, most research focuses on improving the decontamination effect of nanofiltration membranes for separating antibiotics and the like. For example, Chinese patent document with publication number CN105126650A discloses a method for preparing a nanofiltration membrane for separating antibiotics. The invention cross-links and coats polyethyleneimine and gallic acid on the surface of a polyacrylonitrile-based membrane to prepare a nanofiltration membrane for separating antibiotics. The nanofiltration membrane is suitable for the separation of common antibiotics such as cephalexin, tobramycin, clindamycin phosphate, and azithromycin; Chinese patent document with publication number CN115301085A discloses a low-pressure nanofiltration membrane for treating mono / divalent salt and / or antibiotic wastewater and a preparation method thereof. The invention uses aminopiperidine as an aqueous phase monomer and adopts interfacial polymerization to prepare a low-pressure nanofiltration membrane. The introduction of methyl groups that can increase the molecular chain length and asymmetric amino groups promotes hydrogen bonding between the molecular weight of polyamide, thereby increasing the controllability of the internal selective layer, accurately intercepting divalent salt ions, and having good separation performance for antibiotics. Only a few studies have focused on the development of "high-decontamination-low-hardness removal" selective separation technology. A Chinese patent document with publication number CN117258543A discloses a method for constructing an antibiotic desalination nanofiltration membrane based on doctor-coating assisted interfacial polymerization. The nanofiltration membrane is composed of a hydrolyzed polymer membrane support layer and a continuous COFs selective membrane. The COFs selective membrane is prepared by using a doctor blade to uniformly coat a hydrophobic ionic liquid solution containing COFs A monomers on a hydrolyzed polymer membrane rich in an aqueous solution of COFs B monomers, so that COFs A and COFs B monomers undergo a Schiff base reaction at the ionic liquid-water interface. The nanofiltration membrane can be used for the separation of antibiotics and salts, but the invention is relatively complicated to operate, costly, and not conducive to large-scale preparation. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides the application of a specific polyamide nanofiltration membrane for selectively separating new pollutants and salt ions in a water environment. The preparation process of the polyamide nanofiltration membrane is simple and can achieve the separation purpose of "high contamination removal-low hardness removal".
[0006] The specific technical solutions adopted are as follows:
[0007] Application of polyamide nanofiltration membrane in selective separation of new pollutants and salt ions in water environment, the polyamide nanofiltration membrane comprises a polymer ultrafiltration membrane carrier and a polyamide selective separation layer, the polyamide selective separation layer is located on the polymer ultrafiltration membrane carrier; the surface carboxyl density of the polyamide nanofiltration membrane is 60-200 μmol / m 2, zeta potential ≤-20 mV, average effective pore size 0.2-1.0 nm; the new pollutants include at least one of tetracycline, bisphenol A, amoxicillin, diltiazem, erythromycin, roxithromycin, sulpiride, progesterone, and stanozolol; the salt ions include magnesium ions and / or calcium ions; the polyamide nanofiltration membrane has a retention rate of ≥99% for new pollutants in the water environment, and a retention rate of ≤40% for salt ions in the water environment.
[0008] Nanofiltration membranes mainly rely on the antagonism between the pore size screening effect based on the membrane pore size and the Donna effect based on the membrane surface charge to achieve their selective separation function. The present invention regulates the surface negative charge of the polyamide nanofiltration membrane to ensure that the membrane surface has a strong negative charge. The highly negatively charged nanofiltration membrane has a strong attraction for multivalent salt ions, improves the permeability of the nanofiltration membrane to multivalent salt ions, and ensures its high interception rate for new pollutants, improves its selective separation effect for new pollutants and salt ions, so as to achieve the separation purpose of "high decontamination-low hardness removal" in water treatment.
[0009] Preferably, the surface carboxyl density of the polyamide nanofiltration membrane is 60-150 μmol / m 2 ;
[0010] Preferably, the zeta potential of the polyamide nanofiltration membrane is ≤-25 mV.
[0011] Preferably, the average effective pore size of the polyamide nanofiltration membrane is 0.4-0.6 nm.
[0012] Preferably, the surface pore size of the polymer ultrafiltration membrane carrier is between 1 and 200 nm, and the cut-off molecular weight is between 1,000 and 500,000 Daltons.
[0013] Optionally, the polymer ultrafiltration membrane carrier includes a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, a polyvinylidene fluoride ultrafiltration membrane or a polystyrene ultrafiltration membrane.
[0014] Preferably, the preparation method of the polyamide nanofiltration membrane comprises the following steps: preparing an aqueous solution using amine monomers and additives as raw materials, preparing an oil phase solution using acyl chloride monomers as raw materials, depositing the aqueous solution and the oil phase solution on a polymer ultrafiltration membrane carrier in sequence to undergo interfacial polymerization reaction and then heat treating, regulating the mass concentration ratio of the amine monomers in the aqueous solution to the acyl chloride monomers in the oil phase solution to be 0.2-5:1, and preparing the polyamide nanofiltration membrane.
[0015] The structural characteristics and performance characteristics of the polyamide nanofiltration membrane are affected by the aqueous solution and the oil phase solution during the preparation process. Under the specific reaction conditions of the present invention, the nanofiltration membrane has a smaller membrane pore size and a higher membrane surface negative charge. While ensuring that the nanofiltration membrane has a high interception rate for new pollutants, the permeability of the nanofiltration membrane for salt ions is improved, achieving the separation purpose of "high decontamination-low hardness removal".
[0016] The amine monomer is at least one of piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, 2,6-dimethylpiperazine, 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, ethylenediamine, N,N-bis(2-aminoethyl)ethylenediamine, diethylenetriamine and polyethyleneimine.
[0017] Optionally, the additive is at least one of Na3PO4, CuSO4, NiSO4, MgSO4, Al2(SO4)3, sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), and polyethylene glycol octylphenyl ether (Tritonx-100).
[0018] In the aqueous phase solution, the concentration of the amine monomer is 0.01-1wt%, and the concentration of the additive is 0.5-1.5wt%.
[0019] The acyl chloride monomer is at least one of trimesoyl chloride, terephthaloyl chloride, phthaloyl chloride, pyromellitoyl chloride, malonyl chloride, glutaryl chloride, and fumaroyl chloride; the oil phase solvent is at least one of n-hexane, cyclohexane, n-heptane, acetone, toluene, benzene, isopar G, isopar E, isopar H, isopar L, and isopar M.
[0020] Optionally, the concentration of the acyl chloride monomer is 0.01-1 wt %.
[0021] Preferably, the concentration of the amine monomer is 0.1-1wt%, the concentration of the acyl chloride monomer is 0.025-0.25wt%, and the concentration of the additive is 0.5-1.5wt%. Within the above preferred range, the amine monomer and the acyl chloride monomer can form a polyamide separation layer with an appropriate degree of crosslinking, which is conducive to maintaining the balance between its separation performance and interception performance, and the additive can change the water-oil interfacial tension to regulate the interfacial diffusion rate and interfacial distribution of the monomer, further improving the polyamide separation layer structure and membrane performance.
[0022] Preferably, the residence time of the aqueous solution on the polymer ultrafiltration membrane carrier is 10-1000s, further 50-500s; the residence time of the oil phase solution on the polymer ultrafiltration membrane carrier adsorbed with amine monomers is 10-1000s, further 50-500s.
[0023] Preferably, the heat treatment condition is 50-100°C for 5-20 minutes. During the interfacial polymerization reaction, the amine monomer diffuses to the interface of the water and oil phases, and an interfacial polycondensation reaction occurs rapidly. As the reaction time of the amine monomer and the acyl chloride monomer increases, the crosslinking degree increases continuously, and the film thickness also increases continuously. Heat treatment can increase the collision probability of the micro-reactive amine group and the acyl chloride group, thereby increasing the crosslinking degree of the polyamide.
[0024] The present invention also provides a water treatment process with high contamination removal and low hardness removal. The water to be treated contains new pollutants and salt ions. The water to be treated is filtered using the polyamide nanofiltration membrane. During the filtration process, the pre-pressing time is 30-120 minutes and the pressure is 4.0-8.0 bar. The polyamide nanofiltration membrane has a retention rate of ≥99.0% for new pollutants in the water to be treated, and a retention rate of ≤40.0% for salt ions in the water to be treated.
[0025] Preferably, the new pollutant is tetracycline, and the salt ions are magnesium ions.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The polyamide nanofiltration membrane provided by the present invention has a relatively low membrane pore size and a relatively high membrane surface negative charge. The preparation method is simple and easy to implement, the cost is low, and the reaction conditions are mild. It is easy to improve on the basis of the traditional polyamide nanofiltration membrane preparation process to achieve large-scale production. It has a high retention rate for new pollutants and a high permeability for salt ions such as divalent cations. It can selectively separate new pollutants and salt ions in the water environment, thereby achieving the separation purpose of "high pollution removal and low hardness removal".
[0028] (2) The present invention improves the negative charge on the surface of the nanofiltration membrane by regulating the mass concentration ratio of water-oil phase monomers and other polyamide nanofiltration membrane preparation parameters and processes, thereby increasing the permeability of cations in the membrane, and achieving a retention rate of MgCl2 below 40%. At the same time, the nanofiltration membrane prepared by the method of the present invention has a smaller membrane pore size, can effectively separate new pollutants, and has a retention rate of up to 99% for new pollutants. It has excellent separation selectivity for new pollutants / salt ions, and a theoretical separation factor of more than 200 for tetracycline and magnesium ions (common nanofiltration membranes are about 10), and has broad application prospects in the "high-pollution removal-low-hardness removal" water treatment technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 (a) Surface and (b) cross-sectional SEM images of the nanofiltration membrane prepared in Comparative Example 4.
[0030] Figure 2 (a) Surface and (b) cross-sectional SEM images of the nanofiltration membrane prepared in Example 4.
[0031] Figure 3 Schematic diagram of the selective separation process of polyamide nanofiltration membrane. DETAILED DESCRIPTION
[0032] The present invention is further illustrated below in conjunction with the examples and accompanying drawings. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0033] Example 1
[0034] Prepare an aqueous solution with a piperazine concentration of 0.1wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.025wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0035] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0036] The surface carboxyl density of the nanofiltration membrane is 72.45 μmol / m 2 , the zeta potential is -32.14 mV, and the average effective membrane pore size is 0.550 nm.
[0037] Example 2
[0038] Prepare an aqueous solution with a piperazine concentration of 0.1wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.05wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0039] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0040] The surface carboxyl density of the nanofiltration membrane is 72.65 μmol / m 2 , the zeta potential is -33.98mV, and the average effective membrane pore size is 0.542nm.
[0041] Example 3
[0042] Prepare an aqueous solution with a piperazine concentration of 0.1wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.1wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0043] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0044] The surface carboxyl density of the nanofiltration membrane is 72.10 μmol / m 2 , the zeta potential is -32.77 mV, and the average effective membrane pore size is 0.561 nm.
[0045] Example 4
[0046] Prepare an aqueous solution with a piperazine concentration of 0.1wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.25wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0047] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0048] The surface carboxyl density of the nanofiltration membrane is 117.05 μmol / m 2 , the zeta potential is -37.26 mV, and the average effective membrane pore size is 0.560 nm.
[0049] Example 5
[0050] Prepare an aqueous solution with a piperazine concentration of 0.15wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.25wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0051] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0052] The surface carboxyl density of the nanofiltration membrane is 102.30 μmol / m 2 , the zeta potential is -31.81mV, and the average effective membrane pore size is 0.538nm.
[0053] Example 6
[0054] Prepare an aqueous solution with a piperazine concentration of 0.1wt% and a Na3PO4 concentration of 1.5wt% as an aqueous phase solution, and a 0.25wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0055] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0056] The surface carboxyl density of the nanofiltration membrane is 122.60 μmol / m 2 , the zeta potential is -32.22mV, and the average effective membrane pore size is 0.591nm.
[0057] Example 7
[0058] Prepare an aqueous solution with a piperazine concentration of 0.15wt% and a Na3PO4 concentration of 0.5wt% as an aqueous phase solution, and prepare a 0.25wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0059] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0060] The surface carboxyl density of the nanofiltration membrane is 102.60 μmol / m 2 , the zeta potential is -30.12mV, and the average effective membrane pore size is 0.525nm.
[0061] Example 8
[0062] Prepare an aqueous solution with a piperazine concentration of 0.1wt% and a Na3PO4 concentration of 1.0wt% as an aqueous phase solution, and a 0.25wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0063] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0064] The surface carboxyl density of the nanofiltration membrane is 114.65 μmol / m 2 , the zeta potential is -30.38 mV, and the average effective membrane pore size is 0.561 nm.
[0065] Comparative Example 1
[0066] Prepare an aqueous solution with a piperazine concentration of 0.5wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.025wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0067] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0068] The surface carboxyl density of the nanofiltration membrane is 40.85 μmol / m 2 , the zeta potential is -17.63mV, and the average effective membrane pore size is 0.506nm.
[0069] Comparative Example 2
[0070] Prepare an aqueous solution with a piperazine concentration of 0.5wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.05wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0071] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0072] The surface carboxyl density of the nanofiltration membrane is 49.82 μmol / m 2 , the zeta potential is -20.12mV, and the average effective membrane pore size is 0.528nm.
[0073] Comparative Example 3
[0074] Prepare an aqueous solution with a piperazine concentration of 0.4wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a 0.05wt% concentration of trimesoyl chloride (solvent n-hexane) as an oil phase solution;
[0075] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0076] The surface carboxyl density of the nanofiltration membrane is 53.00 μmol / m 2 , the zeta potential is -21.32 mV, and the average effective membrane pore size is 0.531 nm.
[0077] Comparative Example 4
[0078] Prepare an aqueous solution with a piperazine concentration of 0.4wt% and a Na3PO4 concentration of 0.75wt% as an aqueous phase solution, and prepare a trimesoyl chloride (solvent n-hexane) with a concentration of 0.025wt% as an oil phase solution;
[0079] Using a commercial polysulfone ultrafiltration membrane as the porous support membrane, 75 ml of the aqueous solution was poured on the surface of the porous support membrane. After being in contact and standing for 2 minutes, the excess solution was poured off, and a rubber roller was used to remove the residual liquid on the surface. Subsequently, the oil phase solution was slowly and evenly poured onto the surface of the polysulfone ultrafiltration membrane adsorbed with amine monomers. After being in contact and standing for 1 minute 40 seconds, the excess solution on the membrane surface was poured off. The obtained membrane was heat treated in a forced air oven at 80°C for 10 minutes to obtain a nanofiltration membrane.
[0080] The surface carboxyl density of the nanofiltration membrane is 36.83 μmol / m 2 , the zeta potential is -22.75mV, and the average effective membrane pore size is 0.492nm.
[0081] Sample analysis
[0082] The SEM image of the nanofiltration membrane prepared in Comparative Example 4 is as follows Figure 1 As shown in (a) and (b) in FIG. 4 , the SEM images of the nanofiltration membrane prepared in Example 4 are as follows: Figure 2 As shown in (a) and (b) in the figure, the schematic diagram of the selective separation process of polyamide nanofiltration membrane is as follows Figure 3 shown.
[0083] The performance of the nanofiltration membranes prepared in the comparative example and the embodiment was tested at room temperature using a cross-flow flat-plate membrane performance evaluation device, and the pure water flux of the product membrane and the retention rates of 2000 ppm LiCl aqueous solution, 2000 ppm MgCl2 aqueous solution, 2000 ppm Na2SO4 aqueous solution and 10 ppm tetracycline (Tc) aqueous solution were tested respectively.
[0084] In addition, the cross-flow flat-plate membrane performance evaluation device was used at room temperature to test the decontamination and hardness removal performance of the nanofiltration membranes prepared in the comparative example and the embodiment. In order to restore the real application scenario, a mixed solution of 200ppm MgCl2 and 10ppm tetracycline (Tc) was prepared with reference to the groundwater hardness standard, and the selectivity of new pollutants / salt ions in the mixed solution was tested.
[0085] The test temperature was 25 °C, the pressure was 6 bar, and the pre-pressurization was 60 min before the test. The retention rate (%) and separation factor can be calculated by equations (1-1) and (1-2).
[0086] (1-1)
[0087] Among them, R (%) is the retention rate, is the salt ion concentration on the feed side, is the salt ion concentration on the permeate side.
[0088] (1-2)
[0089] in, is the separation factor, , are the retention rates of the two ions, respectively.
[0090] Table 1 Retention rate and theoretical separation factor of nanofiltration membrane for four single salt solutions and tetracycline (Tc) solution in comparative examples and examples
[0091]
[0092] Table 2 Retention rate and theoretical separation factor of nanofiltration membrane for mixed solution of new pollutant (Tc) and salt (MgCl2) in comparative examples and examples
[0093]
[0094] As shown in Table 1, compared with the comparative example, the lithium-magnesium separation factor of the embodiment is reduced, while the density of carboxyl groups on the membrane surface is increased. The zeta potential results show that the negative charge on the membrane surface is enhanced. 2+ The permeability of new pollutants / Mg 2+ The theoretical separation factor is increased, and the theoretical decontamination and hardness removal effect is good (Examples 4 and 5 for Mg 2+ The theoretical selectivity of tetracycline and Mg is more than 200. The actual decontamination and hardness removal data are shown in Table 2. The high negative charge nanofiltration membrane prepared by the method of the present invention has a good selectivity for Mg 2+ The actual selectivity for tetracycline can reach up to more than 200 (Examples 1, 4, 5, 6, 7), which is much higher than that of ordinary commercial nanofiltration membranes (the theoretical separation factor for tetracycline and magnesium ions is about 10).
[0095] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Application of polyamide nanofiltration membrane to selectively separate new pollutants and salt ions in water environment, characterized in that: The polyamide nanofiltration membrane comprises a polymer ultrafiltration membrane carrier and a polyamide selective separation layer, wherein the polyamide selective separation layer is located on the polymer ultrafiltration membrane carrier; the surface carboxyl density of the polyamide nanofiltration membrane is 60-200 μmol / m 2 , zeta potential ≤ -23 mV, average effective pore size 0.2-1.0 nm; the new pollutant is tetracycline; the salt ion is magnesium ion; the polyamide nanofiltration membrane has a retention rate of ≥99% for new pollutants in the water environment, and a retention rate of ≤40% for salt ions in the water environment; The preparation method of the polyamide nanofiltration membrane comprises the following steps: preparing an aqueous solution with amine monomers and additives as raw materials, preparing an oil phase solution with acyl chloride monomers as raw materials, depositing the aqueous solution and the oil phase solution on a polymer ultrafiltration membrane carrier in sequence to undergo interfacial polymerization reaction and then heat treating, regulating the mass concentration ratio of the amine monomers in the aqueous solution to the acyl chloride monomers in the oil phase solution to be 0.2-5:1, and preparing the polyamide nanofiltration membrane; The amine monomer is at least one of piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, 2,6-dimethylpiperazine, 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, ethylenediamine, N,N-bis(2-aminoethyl)ethylenediamine, diethylenetriamine, and polyethyleneimine; the additive is at least one of Na3PO4, CuSO4, NiSO4, MgSO4, Al2(SO4)3, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyethylene glycol octylphenyl ether; The concentration of the amine monomer is 0.1-1wt%, the concentration of the acyl chloride monomer is 0.025-0.25wt%, and the concentration of the additive is 0.5-1.5wt%.
2. The use according to claim 1, characterized in that: The surface carboxyl density of the polyamide nanofiltration membrane is 60-150 μmol / m 2 , zeta potential ≤ -25 mV, and the average effective pore size is 0.4-0.6 nm.
3. The use according to claim 1, characterized in that: The polymer ultrafiltration membrane carrier includes polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polyvinylidene fluoride ultrafiltration membrane or polystyrene ultrafiltration membrane.
4. The use according to claim 1, characterized in that: The acyl chloride monomer is at least one of trimesoyl chloride, terephthaloyl chloride, phthaloyl chloride, pyromellitoyl chloride, malonyl chloride, glutaryl chloride, and fumaroyl chloride; the oil phase solvent is at least one of n-hexane, cyclohexane, n-heptane, acetone, toluene, benzene, isopar G, isopar E, isopar H, isopar L, and isopar M.
5. The use according to claim 1, characterized in that: The residence time of the aqueous phase solution on the polymer ultrafiltration membrane carrier is 10-1000s; the residence time of the oil phase solution on the polymer ultrafiltration membrane carrier adsorbed with amine monomers is 10-1000s.
6. The use according to claim 1, characterized in that: The heat treatment conditions are 50-100°C, 5-20min.
Citation Information
Patent Citations
Antibiotic separating nanofiltration membrane preparation method
CN105126650A
Low-pressure nanofiltration membrane for monovalent / divalent salt and / or antibiotic wastewater treatment and preparation method thereof
CN115301085A
Method for constructing antibiotic desalination nanofiltration membrane based on blade coating method assisted interfacial polymerization
CN117258543A
Method for enhancing lithium-magnesium selectivity of nanofiltration membrane based on cationic surfactant
CN117138579A
Nanofiltration membrane lithium-magnesium separation method based on cationic polyelectrolyte
CN117180983A